Heterogeneidade dos componentes de variância na produção de leite e seus efeitos nas estimativas de herdabilidade e repetibilidade - Valencia Tapia, Elmer Francisco [UNESP]; Ramos, Alcides de Amorim [UNESP]; Wechsler, Francisco Stefano [UNESP]; Lui, Jeffrey Frederico [UNESP]; Grupioni, Natalia Vinhal [UNESP]; Ramos, Salvador Boccaletti [UNESP]; Munari, Dansio Prado [UNESP] (Universidade Federal de Santa Maria (UFSM), 2011)
It was evaluated the heterogeneity of components of phenotypic variance and its effects on the heritability and repeatability estimates for milk yield in Holstein cattle. The herds were grouped according to their level of production (low, medium and high) and evaluated in the non-transformed, square-root and logarithmic scale. Variance components were estimated using a restricted maximum likelihood method based on an animal model that included fixed effects of herd-year-season, and as covariates the linear effect of lactation duration and the linear and quadratic effects of cow's age at calving and the random direct additive genetic, permanent environment and residual effects. In the non-transformed scale all the variance components were heterogeneous. on this scale, residual and phenotypic variance components were associated positively with the level of production while in logarithmic scale that association was negative. Estimates of heritability were more affected than the repeatability for the phenotypic variance heterogeneity and their components. The of selection process efficiency for milk production could be affected by the level of production which was considered for genetic parameters estimation.
Heterogeneity of variance components in milk production and their effects on estimates of heritability and repeatability
Keywords: Dairy cattle; Genetic parameter; heterocedasticity